PENGGUNAAN IMPLIKATUR DALAM MALAM MINGGU MIKO-EPISODE NISSA: TINJAUAN PRAGMATIK - Abdan Ahadiyat; Dadan Rusmana; Sariah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
This article discusses the use of implicature which is a theory put forward by H. Paul Grice, in a comedy web series titled Malam Minggu Miko–Episode Nissa. The purpose of this study is to describe the form of speech that contains implicatures in the series and describe the types of implicatures used. This research uses qualitative descriptive method with Malam Minggu Miko–Episode Nissa series by director Raditya Dika as the object of the research. This research uses data collection techniques with the documentation method that divided into several steps: (1) data reduction, display data and (3) verification data. The researcher uses the data found in the series and then analyse it with implicature theory by Grice and found at least 10 samples which are 7 utterances or questions containing conversational implicatures and 3 utterances or questions containing conventional implicatures.. Key words: implicature, malam minggu miko, web series